Modification of local order in FePd films by low energy He + irradiation - Merkel, D. G.; Tanczikó, F.; Sajti, Sz; Major, M.; Németh, A.; Bottyán, L.; Horváth, Z. E.; Waizinger, J.; Stankov, S.; Kovács, A. (Journal of applied physics, 2008)
Owing to their strong perpendicular magnetic anisotropy, FePd, CoPd, and their Co(Fe)Pt counterparts are candidate materials for ultrahigh density magnetic recording. The stability and magnetic properties of such films are largely dependent on the orientation and local distribution of the L 1 0 FePd phase fraction. Therefore, the formation and transformation of the L 1 0 phase in such thin films have been the subject of continued interest. Highly ordered epitaxial FePd(001) thin films (with an L 1 0 phase fraction of 0.81) were prepared by molecular-beam epitaxy on a MgO(001) substrate. The effect of postgrown room temperature, 130 keV He + irradiation was investigated at fluences up to 14.9 × 10 15